2018
DOI: 10.2741/4627
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen as a template molecule for drug design against Ebola virus

Abstract: The Ebola virus outbreak in West Africa 2015 and Congo 2017, point out an urgent need for development of drugs against this important pathogen. Previously, by repurposing virtual screening of 6438 drugs from DrugBank, ibuprofen was selected as a possible inhibitor of the Ebola virus infection. The results of an additional docking analysis as well as experimental results showing measurable anti-Ebola effect of ibuprofen in cell culture suggest ibuprofen as a promising molecular template for the development of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Previously, the EIIP/AQVN criterion has been proven to be an efficient filter in virtual screening of molecular libraries for candidate inhibitors of HIV and Ebola virus infection (Tintori et al, 2007; Veljkovic et al, 2015a,b). Using this approach, ibuprofen was selected as an inhibitor of the Ebola virus infection, and this prediction was later experimentally confirmed (Zhao et al, 2016; Paessler et al, 2018. )…”
Section: Discussionmentioning
confidence: 96%
“…Previously, the EIIP/AQVN criterion has been proven to be an efficient filter in virtual screening of molecular libraries for candidate inhibitors of HIV and Ebola virus infection (Tintori et al, 2007; Veljkovic et al, 2015a,b). Using this approach, ibuprofen was selected as an inhibitor of the Ebola virus infection, and this prediction was later experimentally confirmed (Zhao et al, 2016; Paessler et al, 2018. )…”
Section: Discussionmentioning
confidence: 96%
“…The WHO has indicated that there is no evidence to confirm an aggravation of COVID-19 infection with the administration of NSAIDs [30,31]. In fact, it has been reported that some NSAIDs could have some type of activity against viruses such as VZV [32], HCMV [32], HSV-1 [33], influenza virus A⁄ H1N1 subtype [34,35], VSV [36,37], EBOLA [38,39], HIV [40], JEV [41], CHIKV [42], SARS-CoV-1 [43], and recently against SARS-CoV-2 [35,44,45]. Additionally, many studies have been carried out that propose various targets for blocking virus recognition, importation and replication processes through the use of reused drugs, immunotherapies, interference strategies and various inhibitory compounds [46].…”
Section: Introductionmentioning
confidence: 99%
“…Antiinflammatory compounds, including nonsteroidal antiinflammatory drugs (NSAIDs), can control fever and other aspects of the “cytokine storm” that several different viruses induce. Ibuprofen has been suggested to control Ebola symptoms . NSAIDs can also improve survival in cancers, for example in patients with activating mutations in PIK3CA, which are very common in head and neck cancers.…”
Section: Finding New Uses For Approved Drugsmentioning
confidence: 99%